2012
DOI: 10.5505/tjtes.2012.99075
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 protease inhibitor and antichymotrypsin levels in acute pancreatitis

Abstract: AMAÇŞiddetli formundaki yüksek mortalite oranı ile akut pankreatit günümüzde halen tıbbın önemli bir sorunudur. Hastalığın şiddetinin erken belirlenmesi etkin tedavi için kritik öneme sahiptir. Çeşitli biyokimyasal belirteçler denenmiştir ve halen denenmektedir. İdeal belirteç olguyu tanı-yabilmeli ve pankreatitin hafif ve şiddetli formlarını ayırt edebilmelidir. GEREÇ VE YÖNTEMBu prospektif çalışmaya akut pankreatitli 34 olgu (14 erkek, 20 kadın, ort. yaş: 58 yaş) ve kontrol grubundaki 33 olgu (17 erkek, 16 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…We identified 14 down-regulated proteins or isoforms and four up-regulated proteins in HSAP rat models. Serum levels of AAT, an acute-phase reactant previously showed to be elevated in the serum of patients and animals in the early phase of AP 22 23 24 25 26 , were found to be significantly depressed in HSAP rats compared with NHSAP rats. A previous study suggested that AAT has significant anti-inflammatory properties by affecting a wide range of inflammatory cells such as neutrophils, monocytes, macrophages, and mast cells 36 .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We identified 14 down-regulated proteins or isoforms and four up-regulated proteins in HSAP rat models. Serum levels of AAT, an acute-phase reactant previously showed to be elevated in the serum of patients and animals in the early phase of AP 22 23 24 25 26 , were found to be significantly depressed in HSAP rats compared with NHSAP rats. A previous study suggested that AAT has significant anti-inflammatory properties by affecting a wide range of inflammatory cells such as neutrophils, monocytes, macrophages, and mast cells 36 .…”
Section: Discussionmentioning
confidence: 83%
“…2c ). We chose to further investigate the expression of AAT, a 52-kD protein previously involved in the pathology of AP 22 23 24 25 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, although several of these marker candidates showed promising associations with the severity of AP in humans, reported data are conflicting, with differences among studies in optimal sampling time points, short half-life of some markers (eg, αMGs-trypsin complexes), various tissue protease sources (eg, neutrophil polymorphonuclear elastase) and assay differences. 18,22 In dogs, α 2 MG concentration was significantly decreased in spontaneous AP compared to healthy controls, but was a poor disease severity indicator and was only weakly negatively correlated (r = −.147) with serum trypsin-like immunoreactivity concentration. 23 In another study of dogs with various diseases, α 1 PI concentration was normal, or even increased, in AP cases, 24 in contrast to the hypothesized trend.…”
Section: Introductionmentioning
confidence: 96%
“…It is easily ignored or misdiagnosed at an early stage, and non-surgical therapy remains the major treatment [2,3]. It has been found that effectively inhibiting the activation and release of pancreatin, cell factors, and inflammatory factors; improving the microcirculation; and adjusting the internal environment in the early period are of great significance in the prognosis of severe acute pancreatitis [4].…”
Section: Introductionmentioning
confidence: 99%